Using the pathogen-host interactions database (PHI-base) to investigate plant pathogen genomes and genes implicated in virulence - Urban, Martin; Irvine, Alistair G.; Cuzick, Alayne; Hammond-Kosack, Kim E. (Frontiers in Plant Science, 2015)
New pathogen-host interaction mechanisms can be revealed by integrating mutant phenotype data with genetic information. PHI-base is a multi-species manually curated database combining peer-reviewed published phenotype data from plant and animal pathogens and gene/protein information in a single database.